Studi Komparasi Implementasi Kurikulum Pada Pembelajaran Akselerasi Dan Pembelajaran Reguler (Kajian Pada Kelas Xi Ci+Bi Ipa Dan Kelas Xi Ipa Di Sman 1 Padang) - Rifmasari, Yessi (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2017)
The study was based on differences in the characteristics of accelerated learners and regular learnes in learning activites. Where, learners are capable of far above this average, usually often seemed relaxed and seemed less attention to the lesson. What is even worse, learners tend to disturb her so that teaching and l earning activities in the classroom becomes less smooth. Therefore, to serve the students in learning activities required different curriculum implementation at both learning in order to achieve the expected competencies. This study aimed to describe whether there are significant differences between the grades XI CI + BI learning and learning XI IPA grades in science subjects. This research approach that uses quantitative approaches. While the results of learning outcomes research using quantitativeapproach that is no significant difference between the grades of accelerated learning XI CI + BI with grades of regular learning XI IPA in science subjects.Keywords: accelerated learning, regular learning, curriculum implementation